THE APPLICATION OF INNOVATIVE TECHNOLOGIES IN TEACHING FOREIGN LANGUAGES - Saidkazieva Diyora Atabekovna (Journal of new century innovations, 2023)
Abstract: This article highlights using innovative technologies to make the educational process more effective. Innovative technologies like gamification, the application of mobile apps and even virtual reality, can significantly improve learners' receptive and productive skills, which can engage them to communicate effectively in various contexts. Overall, the effective usage of innovative technologies presents a practical approach to language instruction that can enhance learners' communicative competence.